The plot against America [videorecording (DVD)] : an HBO limited series / created by David Simon and Ed Burns. - Ryder, Winona, 1971-; Boyle, Anthony, 1994-; Kazan, Zoe, 1983-; Spector, Morgan, 1980-; Kostroff, Michael; Krumholtz, David, 1978-; Roth, Philip (HBO, 2020)
The Levins are a working-class Jewish family in Newark, New Jersey in an Alternate America during WWII, observing the political rise of aviation hero Charles Lindbergh, a xenophobic populist who captures the presidency in 1940 and turns the nation toward fascism.